A comparison of technologically mediated and face‐to‐face help‐seeking sources. (1st August 2015) - Reeves, Philip M.; Sperling, Rayne A.
Abstract : Background: Current post‐secondary school students have access to multiple help‐seeking sources. As help‐seeking behaviour relates to academic achievement, the provision of preferred help sources would be beneficial to students, instructors, and course designers. Aims: This study examines whether students prefer and intend to utilize technologically mediated or face‐to‐face help‐seeking sources. Sample: Participants ( n  = 226) were recruited from two sections of an on campus, introductory, educational psychology class. Methods: An online survey was distributed containing measures of help‐seeking threat, adaptive help‐seeking tendencies, avoidant help‐seeking tendencies, and the intention to seek help from six sources. Correlations and an ANOVA were calculated to determine whether source preferences differed by self‐reported course grade. Results: Help‐seeking threat was only negatively associated with sources of help that required face‐to‐face interaction. Despite the threat, students intended to use face‐to‐face help‐seeking sources more than technologically mediated sources. Students intended to seek help the most before or after class, via email, or during class. Students intended to seek help the least through the discussion board and during online office hours. Higher performing students preferred face‐to‐face sources, particularly before or after class and during class, more than lower performing students. Lower performing students intended to use mediated sources especially the discussion board and online office hours more than the higher performing students. Conclusions: The results provide new insights into the help‐seeking process and suggestions for instructors when allocating time and classroom resources. Additionally, the study illustrates the need for continual refinement of a help‐seeking source classification system.